Reciprocal control in adaptive environments - Jäger, Nils; Schnädelbach, Holger; Hale, Jonathan; Kirk, David; Glover, Kevin (Oxford University Press, 2017)
Computing has become an established part of the built environment augmenting it to become adaptive. We generally assume that we control the adaptive environments we inhabit. Using an existing adaptive environment prototype, we conducted a controlled study testing how the reversal of control (where the environment attempts to influence the behaviour of the inhabitant) would affect participants. Most participants changed their respiratory behaviour in accordance with this environmental manipulation. Behavioural change occurred either consciously or unconsciously. We explain the two different paths leading participants to behavioural change: (1) We adapt the model of interbodily resonance, a process of bodily interaction observable between, for example, partners engaged in verbal dialogue, to describe the unconscious bodily response to subtle changes in the environment. (2) And we apply the model of secondary control, an adjustment of one’s own expectations to maintain the pretence of control, to describe conscious cognitive adaptation to the changing environment. We also discuss potential applications of our findings in therapeutic and other settings.